Il diritto dei minori alla libertà religiosa: tra norme e prassi internazionali (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Brevi cenni sul contesto normativo internazionale - 3. La valenza della prassi internazionale: in particolare, il ruolo degli organismi internazionali indipendenti - 4. La giurisprudenza della Corte europea dei diritti dell’uomo e la rilevanza delle convinzioni religiose dei genitori - 5. Segue: il rispetto del diritto all’educazione dei minori - 6. Il limitato rilievo dei principi generali a tutela dei minori e la necessità di riconoscere loro un locus standi in sede processuale.Children's right to religious freedom: between international norms and practiceABSTRACT: Religious freedom is considered a cornerstone of democratic societies, a vital element that contributes to forming the identity of believers and, with reference to minors, the course of their education and upbringing, accompanying them to adulthood. In international law studies, the right of minors to religious freedom, understood as the set of international obligations imposed on States, in both the negative and positive senses inherent in its achievement, has been little explored. The paper aims to identify systematic elements to help reconstruct the “minimum” content of a child’s right to religious freedom, pursuing two main lines of investigation: one relating to the exercise of freedom of worship in the various social contexts in which minors grow up; the other inherent in the educational project that leads them to adulthood. Recognition of the child of a locus standi in the independent court of law compared to that of the family members in charge of his care will help to realize the subjectivity of the child even in such a sensitive subject matter as religious freedom.